“Beyond Guarding: Silent forces in action.” Historical shifts in the South African private security industry, c. 1957-2024 - Vivier, Jacques Mulder (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.